When falsification is the only path to truth - BYRNE, RUTH MARY JOSEPHINE (Mahwah, NJ: Lawrence Erlbaum Associates, 2005)
Can people consistently attempt to falsify, that is, search for refuting evidence, when testing the truth of hypotheses? Experimental evidence indicates that people tend to search for confirming evidence. We report two novel experiments that show that people can consistently falsify when it is the only helpful strategy. Experiment 1 showed that participants readily falsified somebody else?s hypothesis. Their task was to test a hypothesis belonging to an `imaginary participant? and they knew it was a low quality hypothesis. Experiment 2 showed that participants were able to falsify a low quality hypothesis belonging to an imaginary participant more readily than their own low quality hypothesis. The results have important implications for theories of hypothesis testing and human rationality.
Proceedings of the 27th Annual Conference of the Cognitive Science Society
PUBLISHED
Keywords: Psychology